2016
DOI: 10.1093/humrep/dew323
|View full text |Cite
|
Sign up to set email alerts
|

Transgender men's experiences of fertility preservation: a qualitative study

Abstract: N/A.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
159
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 180 publications
(163 citation statements)
references
References 22 publications
2
159
0
2
Order By: Relevance
“…In another interview‐based survey of nine transgender persons and their partners (n = 11) who had experienced assisted reproduction services, several institutional barriers to satisfy the needs in this population, such as a lack of awareness and insufficient training of healthcare providers, were identified. Armuand et al prospectively followed 15 adult transgender men (age range 19‐35 years) undergoing oocyte preservation; the study participants reported the recrudescence of gender dysphoria upon interruption of testosterone treatment, during hormonal stimulation and/or while being exposed to pelvic examinations. The study further showed that the distress experienced by transgender persons could be alleviated in the presence of a supportive healthcare environment.…”
Section: Methodsmentioning
confidence: 99%
“…In another interview‐based survey of nine transgender persons and their partners (n = 11) who had experienced assisted reproduction services, several institutional barriers to satisfy the needs in this population, such as a lack of awareness and insufficient training of healthcare providers, were identified. Armuand et al prospectively followed 15 adult transgender men (age range 19‐35 years) undergoing oocyte preservation; the study participants reported the recrudescence of gender dysphoria upon interruption of testosterone treatment, during hormonal stimulation and/or while being exposed to pelvic examinations. The study further showed that the distress experienced by transgender persons could be alleviated in the presence of a supportive healthcare environment.…”
Section: Methodsmentioning
confidence: 99%
“…Indeed, procedures required for obtaining fertility preservation (i.e. hormonal ovarian stimulation and transvaginal ultrasound that is a genitalia-speci c procedure) may be experienced by transmen as having a negative impact on their gender dysphoria [39]. These procedures may heighten feelings of dysphoria, thus challenging the break up with the transgender people's old gender identity.…”
Section: Barriers Related To Dysphoriamentioning
confidence: 99%
“…Some transgender people may use several coping strategies, 'such as focusing on the reasons for undergoing fertility preservation, reaching out to friends and family for support and the cognitive approaches of not hating their body or using non-gendered names for their body parts.' [39]. Note, however, that the negative psychological effects of FP for transgender individuals may be caused by several reasons.…”
Section: Barriers Related To Dysphoriamentioning
confidence: 99%
“…Some transgender men who temporarily discontinued testosterone to pursue fertility preservation experienced worsening gender dysphoria with resumption of menses, whereas others felt the experience was less distressing than anticipated. 65 In previously studied samples of transgender adults, 38% of transgender men 59 and 51% of transgender women 60 indicated they would have considered gamete (ie, sperm or egg) cryopreservation if this technology had existed and been offered to them. Among transgender women, identifying as lesbian or bisexual and younger age are associated with greater likelihood of considering sperm cryopreservation.…”
Section: February 2019mentioning
confidence: 99%